STUDENTS’ MOTIVATION IN LEARNING ENGLISH DURING PANDEMIC COVID-19AT SMA NEGERI 1 TELUKDALAM - Laiya, Rebecca E.; Zagoto, Impiani; Sarumaha, Anastasia Yanilia (Research on English Language Education, 2022)
In this situation the process of learning is not running as well as usual because of pandemic covid-19, it makes the students’ motivation in learning English disturbed and the students faced the different situation and they should do E-learning process. This research aimed to know the types students learning motivation and the percentage of high and low the students learning motivation during the pandemic covid-19. during pandemic covid-19 namely intrinsic motivation and extrinsic motivation and students motivation in SMA N.1 Telukdalam was high in this pandemic situation. Every difficult proccess and the different situation, they used it as a big motivation to do learning, to search more about their material, to do their homework for sure, because they know that they should face this pandemic covid-19 through learning for sure., the students should motivate themselves to learn more, and make there daily activity fun at e-learning. For students who faced pandemic Covid-19 students should be students it self and be consistent.